Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s13293-017-0158-2
|View full text |Cite
|
Sign up to set email alerts
|

SP-A2 contributes to miRNA-mediated sex differences in response to oxidative stress: pro-inflammatory, anti-apoptotic, and anti-oxidant pathways are involved

Abstract: BackgroundHuman innate host defense molecules, surfactant protein A1 (SP-A1), and SP-A2 differentially affect the function and proteome of the alveolar macrophage (AM). We hypothesized that SP-A genes differentially regulate the AM miRNome.MethodsHumanized transgenic mice expressing SP-A1 and SP-A2 were subjected to O3-induced oxidative stress (OxS) or filtered air (FA), AMs were isolated, and miRNA levels were measured.ResultsIn SP-A2 males, we found significant changes in miRNome in terms of sex and sex-OxS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(96 citation statements)
references
References 79 publications
(82 reference statements)
7
88
1
Order By: Relevance
“…SP-A2 was recently shown to regulate microRNA, which we speculate could in turn regulate the SP-A and SP-D expression. 33 The results derived from the human donor PCLS model were different from the findings using the human lung cancer cell model with an SP-A1/SP-A2 genotype 6A 4 6A 4 /1A 5 1A 5 . The cell line showed a significant reduction of SP-A expression when methylprednisolone was used at high doses (Figure 1), but this was not observed at low doses.…”
Section: Methylprednisolone Treatedmentioning
confidence: 62%
“…SP-A2 was recently shown to regulate microRNA, which we speculate could in turn regulate the SP-A and SP-D expression. 33 The results derived from the human donor PCLS model were different from the findings using the human lung cancer cell model with an SP-A1/SP-A2 genotype 6A 4 6A 4 /1A 5 1A 5 . The cell line showed a significant reduction of SP-A expression when methylprednisolone was used at high doses (Figure 1), but this was not observed at low doses.…”
Section: Methylprednisolone Treatedmentioning
confidence: 62%
“…Recent animal studies have shown that not only SP-A1 and SP-A2 variants distinctively affect the alveolar macrophage miRNome [25], but most relevantly they also differentially affect lung function and survival after infection [26,27]. It is therefore conceivable that SP-A gene variants may contribute to the complex etiologic pathogenesis of lung allograft dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, however, unlike in rodents, there are two genes, Sftpa1 and Sftpa2, encoding SP-A1 and SP-A2, respectively, and these two gene products have been shown to have a differential impact on several AM functions. These functions include bacterial phagocytosis and cytokine production by AM [18,24,25], actin polymerization in the AM [7], and effects on the AM proteome and miRNome [26][27][28]. Moreover, the effects of SP-A variants on the regulation of the AM proteome and miRNome, survival, and pulmonary mechanics after infection, vary with sex [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%